A volatilidade do fluxo de capital para economias emergentes: O papel da qualidade institucional do governo e do desenvolvimento do sistema financeiro doméstico - Kátia Rocha; Ajax Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The paper proposes a panel model to the determinants of capital flow volatility to a group of eighteen emerging market economies (EME) in the period of 2000 to 2011. It studies the robustness of the model regarding different volatility measures; analyses several types of gross capital inflow; focusing the role of government institutional quality and the development of domestic financial system (banks, insurance companies, and capital markets - stocks, bonds and derivatives). The eighteen EME analyzed (Argentina, Brazil, Chile, Colombia, Czech Republic, Hungary, India, Indonesia, Malaysia, Mexico, Peru, Philippines, Poland, Russia, South Africa, Thailand, Turkey and Venezuela) represented roughly 95% of the Emerging Markets Bond Index Global (EMBIG) in January 2013, being the biggest destination to international capital flow to EME according to the report of the Bank for International Settlements (BIS, 2009). The main conclusion suggests that a reduction of capital flow volatility can be achieved by the adoption of policies that improve government institutional quality and promote development, stability and efficiency of the domestic financial system.
Keywords: F21; F36; G38; C23; 330; capital flow; emerging markets; institutional quality of the government; development of domestic financial system